Manajemen Risiko Rantai Pasok Bahan Baku Fast Moving pada PT Inkor Bola Pasific Menggunakan Model Supply Chain Operation Reference dan Metode House of Risk - Renata Viviana Immyawahyu; Teguh Oktiarso (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2022)
Pacific Ball Inkor is facing several problems in their raw material supply activities such as stock accumulation, materials not passing the test, and delayed production process. To prevent potential risks, this research aims to identify and analyze risk agents using the Supply Chain Operation Reference model and House of Risk method. The study found 17 risks and 13 risk agents, and 9 selected risk agents were analyzed in HOR Phase 2 to obtain mitigation strategies. Finally, 12 mitigation strategies were obtained, which could be helpful for the company to manage and prevent potential risks. This research emphasizes the importance of risk identification and analysis in the supply chain management to minimize the impact of potential risks on the company's operations.